2017
DOI: 10.2737/fpl-gtr-248
|View full text |Cite
|
Sign up to set email alerts
|

Measuring wood quality in standing trees--a review

Abstract: This report summarizes a state-of-the-art review conducted on the topic of field measurement of the quality of wood in trees. The foundation science of micro-resistance drilling and acoustic-based techniques for use with woody materials is presented, and use of these techniques for the detection of biodeterioration in wood is discussed. Quantification of the physical and mechanical properties of wood, in standing timber, is reviewed. Studies designed to examine the use of these techniques with trees are summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The results are listed in Tables 1 and 2. The measurement accuracy (MA) in the table is calculated by Equation (13).…”
Section: Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are listed in Tables 1 and 2. The measurement accuracy (MA) in the table is calculated by Equation (13).…”
Section: Test Resultsmentioning
confidence: 99%
“…The detection of the tree density can be realized using this stress wave technique. However, this detection equipment has relatively low detection accuracy, and it can only identify the rot and holes present in the tree, but not the annual rings or other small density changes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Legg and Bradley [47] provided a thorough review of the literature concerning the stiffness of trees, logs and lumber. Acoustic methodology was reviewed by [46,48].…”
Section: Methods In the Low-frequency Domain For Elastic Constant Det...mentioning
confidence: 99%
“…A number of studies have also demonstrated the effectiveness of acoustic methods for NDE of standing trees (Senalik et al, 2014, Rudnicki et al, 2017, which could be useful for improving the efficiency and usable yield of harvests of whole timber for construction purposes.…”
Section: Acoustic Methodsmentioning
confidence: 99%